Understanding Hepatotoxicity (IntechOpen, 2026)
This book provides a comprehensive overview of the causes, symptoms, and prevention of hepatotoxicity. It includes two sections. The first section focuses on drug-related hepatotoxicity and includes four chapters that summarize glucocorticoids for the treatment of acute severe drug-induced liver injury, review various pharmacological therapies for drug-induced liver injury, discuss the role of gut microbiota in the management of drug-induced liver injury, and introduce the significance of dual-energy computed tomography for the evaluation of amiodarone-induced hepatotoxicity. The second section focuses on hepatotoxicity in other aspects, including two chapters that review metabolic hepatic alterations and diseases under hypoxic conditions, and explore the hepatoprotective activity of proline derivatives. This book is a valuable resource for physicians and scientists seeking to enhance their understanding of hepatotoxicity.